Phytophthora infestans Cholinephosphotransferase with Substrate Specificity for Very-Long-Chain Polyunsaturated Fatty Acids - Chen, Yan (American Society for Microbiology, 2013)
The effective flux between phospholipids and neutral lipids is critical for a high level of biosynthesis and accumulation of very-long-chain polyunsaturated fatty acids (VLCPUFAs), such as arachidonic acid (ARA; 20:4n-6), eicosapentaenoic acid (EPA; 20:5n-3), and docosahexaenoic acid (DHA; 22:6n-3). Here we describe a cDNA (PiCPT1) from Phytophthora infestans, a VLCPUFA-producing oomycete, that may have a role in acyl trafficking between diacylglycerol (DAG) and phosphatidylcholine (PC) during the biosynthesis of VLCPUFAs. The cDNA encodes a polypeptide of 393 amino acids with a conserved CDP-alcohol phosphotransferase motif and approximately 27% amino acid identity to the Saccharomyces cerevisiae cholinephosphotransferase (ScCPT1). In vitro assays indicate that PiCPT1 has high cholinephosphotransferase (CPT) activity but no ethanolaminephosphotransferase (EPT) activity. Substrate specificity assays show that it prefers VLCPUFA-containing DAGs, such as ARA DAG and DHA DAG, as substrates. Real-time PCR analysis reveals that expression of PiCPT1 was upregulated in P. infestans organisms fed with exogenous VLCPUFAs. These results lead us to conclude that PiCPT1 is a VLCPUFA-specific CPT which may play an important role in shuffling VLCPUFAs from DAG to PC in the biosynthesis of VLCPUFAs in P. infestans.